Relative Deprivation as a Factor of Sociopolitical Destabilization: Toward a Quantitative Comparative Analysis of the Arab Spring Events. (April 2020) - Korotayev, Andrey V.; Shishkina, Alisa R.
The article analyzes relative deprivation as a possible factor of sociopolitical instability during the Arab Spring events using the methods of correlation and multiple regression analysis. In this case, relative deprivation is operationalized in two ways: (a) through the indicator of subjective feeling of happiness on the eve of the events of the Arab Spring, and (b) through the scale of decrease of the subjective feeling of happiness on the eve of the events of Arab Spring. It is shown that the change in the level of subjective feeling of happiness between 2009 and 2010 is a powerful, statistically significant predictor of the level of destabilization in Arab countries in 2011. The next most powerful predictor is the mean value of the subjective feeling of happiness in the corresponding country for 2010. At the same time, the fundamental economic indicators we tested, while controlling for them, have turned out to be extremely weak and at the same time statistically insignificant predictors of the level of sociopolitical instability in the Arab countries in 2011.